Prevalence And Analysis Factor Risk of Oral Stomatitis In Malays Ethnicity in Indonesia: Panel Data Analysis - Abu Bakar (Indonesian Journal of Dentistry, 2023)
Indonesia Family Life Survey (IFLS) was used to formulate various policy government . In that survey, respondents were also asked about experience experience thrush (oral stomatitis) during four last week . Objective of this study is to analyze relationship of several risk factors with incident of oral stomatitis of Malays in Indonesia. This cross-sectional study done based on the data obtained from IFLS in 2014. Data analysis used excel software ( univariate data ) and IBM SPSS version 25. Prevalence of oral stomatitis in ethnic Malays in Indonesia are 11% (26 cases of 236 respondents) . Analysis results SPSS shows not significant relationship between age , gender , place residence , education and economic status with incidence of oral stomatitis. There is significant relationship between condition health general with incidence of oral stomatitis (p < 0.05). Study results recommend necessity look after and care cleanliness cavity mouth in patients who have unhealthy condition.